The campa ashaninka pottery: knowledge and symbolism of a feminine technology in process of replacement - Rojas Zolezzi, Enrique (2021)
The present article is a description of the techniques of production and symbolism of the production of pottery among the campa ashaninka of the peruvian Amazon. The process of replacement of this technology and its consequences for the relations between husbands and wives is also studied.